Evaluation of Solar radiation in humid subtropical climatic belt in north India - R. S. Mishra, Harsh Kadyan, Anil K. Berwal, (Design Engineering, 2021)
In this study, one year data measurements for the solar radiation (January 2016 to December 2016) was performed in India for the city of Sonipat of SRRA station, Deenbandhu Chhotu Ram University of Science & Technology(DCRUST), Murthal, Haryana. During this study consist global radiations, direct radiations, diffuse radiations and other parameters like relative humidity and ambient temperature is investigated. Data investigation shows Study area received good solar radiations in the months of February to October. In the month of June 2016 maximum global radiations is 250.64 W/m2 associated ambient temperature is 30.08°C and minimum values found global radiations in month of December 2016 is 88.96 W/m2 with ambient temp is 14.86°C. Relative humidity is found low in the early months of year (February to June) and during this time study area receives good amount of direct radiations. Moreover, the ambient temperature found to be on lower side in winter time and relative humidity is high. So relative humidity and direct radiations shows good correlation as direct radiations increases when relative humidity decreases.